Wpływ regulacji środowiskowych na działalność przedsiębiorstw - Ciechelska, Agnieszka; Poskrobko, Tomasz (The influence of environmental regulations on the activity of enterprises, 2006)
Nowadays, sustainable development is the imperative issue in creating the quality of human life. Enterprises have the significant role in this process - on the one hand the enterprises can generate benefits connected with economics profits, and on the other - environmental and social costs. In many countries, especially high developed, there are a lot of instruments persuading enterprises to minimize the negative impacts. There could be economic, obligatory or voluntary instruments. Voluntary actions in enterprises play'more and more important role in the globalization time and high-developed economy connections on international markets. The basis of such actions is the moral pressure. And what is remarkable, the instruments like that can prevent ecodumping and ecoimperialism in an effective way.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 85-94